Ventilation limited extinction of fires in ceiling vented compartments. (December 2015) - He, Qize; Ezekoye, Ofodike A.; Li, Changhai; Lu, Shouxiang
Highlights: The oxygen supply condition was found mainly control the fire self-extinction. A self-extinction boundary was found for the ceiling vented compartment. A ventiltion paramter derived from normalisation dentifis th ventilation condition. The oxygen concentration and gas temperature were strong functions of the ventilation parameter. Abstract: Compartment fire behaviour under ceiling ventilation was experimentally investigated in a reduced-scale compartment. Different fuels, including methane, propane, N-heptane, ethanol and N-butanol, covering both gas and liquid phase fuels were used in the experiments. Measurements included gas fuel flow rate, pool fire Mass Loss Rate, gas temperature, and gas mole fraction. The fire development processes in ceiling vented compartments were described using energy and species balances. The influence of both the vent size and the fire size on energy and species transfer was examined. A ventilation limited extinction boundary was found for ceiling vented compartments and the general self-extinction processes were represented. The experimental results were plotted using a ventilation parameter ( A v 5 / 4 / Q ̇ f ) derived from balance equations. It was found that this parameter can be used to identify the general ventilation condition in ceiling vented compartments. The oxygen concentration and gas temperature were shown to depend on the ventilation parameter.